Association between cardiovascular disease parameters and chronic periodontitis - Kamil, Wisam Alaa; Hilal Abbood Al-Bayati, Lina; Mohamed Ali, Suhaila (2015)
Aim: The aim of this study was to investigate the association between cardiovascular risk markers and chronic periodontitis. Material and Methods: A total of 40 healthy individuals were included in this case control study and categorized into two groups of 20 subjects each. Of these, 20 patients were controls with no clinical attachment loss and 20 patients had chronic periodontitis. Detailed clinical periodontal parameters were recorded from all participants. Serum samples were collected for the evaluation of high sensitive CRP (Hs-CRP) and lipids. The leukocyte (WBC) parameters were evaluated from peripheral blood samples. Results: Statistically significant differences were detected between both groups in respect to leukocyte counts and serum Hs-CRP levels (p-value=0.003 and <0.001 respectively). There were no significant differences between serum lipid levels of the case and control groups. Conclusions: The local periodontal inflammation may influence the systemic inflammation level by increasing the serum Hs-CRP and leukocytes count in patients with chronic periodontitis.